Behavioral Management of Blockchain Technology for Indonesia MSMEs Managers - Mutamimah Mutamimah; Nur Aisyah; Diana Diana; Akbar Nuur Purnama Darma Wahana (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2026)
This research aims to test behavioral management for Indonesia MSMEs Manager on blockchain technology (BT), with digital financial literacy (DFL) as a moderating. Determinants of behavioral management as behavioural intention: perceived usefulness, perceived easy to use, social influence and responsiveness. The population in this research is all MSMEs in Indonesia dan sampling technique uses purposive sampling. Statistical analysis uses Moderated Regression Analysis. The research found that behavioural management (1) perceived usefulness had a positive effect while perceived ease of use had a negative effect on the behavior intention of MSMEs in adopting (BT); (2) Social influence and responsiveness have no effect on MSMEs' behavioral intention in adopting BT; (3) DFL is able to strengthen the influence of perceived ease of use and social influence, but weakens the influence of perceived usefulness on the behavior intention of MSMEs in adopting BT; and (4) the behavior intention of MSMEs in adopting BT has a positive effect on actual use.